Detection of Toxoplasma gondii in domestic turkey (Meleagris galbpavo) in Basrah Province using Serological methods - Ameer Ibrahim Abdulzahra (Basrah Journal of Veterinary Research)
Toxoplasma gondii, a parasite found extensively in humans and various animals, including domestic poultry, is widely distributed across the globe. Its ability to invade host cells depends on a special combination of cytoskeletal and secretory organelles. Meat from infected poultry, such as turkey and chicken, is widely consumed worldwide and is the primary source of T. gondii infection in humans, however, scant information exists regarding the prevalence of T. gondii in domestic turkey (Meleagris galbpavol) in Iraq. In this study, antibodies against T. gondii were investigated in 38 M. galbpavol randomly from different areas of Basrah Province utilizing the latex agglutination test (LAT) and T. gondii (Toxo) IgM/IgG Antibody Rapid Test and Enzyme Linked Immunosorbent Assay (ELISA). T. gondii antibodies (LAT) were discovered in 14 (36.84%) of the 38 samples, whereas T. gondii antibodies (Rapid Test) were found in 8 (21.05%), As for the ELISA test were found 7(18.42%) infected. High rates of toxoplasmosis in Basrah Province indicate soil contamination with the Oocysts of parasite, which can be attributed to the presence of cats and turkeys in the same locations. Depending on the present results, the turkey meat may be representing a significant source of human T. gondii infection in the studied area. This is the first study in Basrah province to detect Toxoplasmosis in M. galbpavol by using serological methods.